A Co-joint Deterministic Search Direction Sampling Procedure with Probabilistic Soft Approach - Ismail bin Mohd.; GOH KHANG Wen; TAN EE LING (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2009)
Since hard continuous optimization models contain more than one solution and even continuumsolution, it is impossible to seek all the solution by using the existent optimization methods.Therefore, in this paper we introduce a co-joint deterministic and probabilistic approach whichmodifies a soft approach for solving hard continuous optimization models. An algorithm of co-jointapproach and several numerical experiments have been presented in this paper. The specialnumerical test results have shown that the co-joint approach is more effective than soft approachalgorithm. Fortunately, we have found that the co-joint algorithm can be used to determine whetherthe optimization model is hard continuous optimization models or not.